(untitled) (Research, Society and Development, 2020)
The Azadirachta indica A. Juss, better known as Neem (Meliaceae family), is a fruit which have been identified over 40 terpenoids. These have against insects, the most efficient of them azadirachtin. Knowing this, it is important to characterize the fruits of Neem, thus verifying its composition. Was collected 180 Neem fruits in two maturation stages (green and mature). The experimental design used was completely randomized with 2 treatments composed by maturation stages green and mature. We used 80 fruits of Neem to each stage of maturation with the plot being composed of 4 replications of 20 fruits. It can be concluded that the nim has a high content of carbohydrates (in two maturation stages), which has considerable soluble solids concentration, with emphasis to the mature fruit, and yet, high energy value. It was possible to observe from these results, that is necessary to do the fruit toxicological study, to know if it is possible to use it for human consumption, whether in the food industry or the gastronomy as an NCFP (non-conventional food plant), for example, or the isolation of the compound.